Rancang Bangun Incline Vibrating Screen Pengolahan Minyak Kelapa Sawit Kapasitas 2 Ton/Jam - St Nugroho Kristono (Politeknik Kelapa Sawit Citra Widya Edukasi, 2017)
The process of purifying the palm oil from the press, firstly done filtering process. Filtering process is an important process to obtain the smooth and soft results of a product. Several models have been developed for the filtering of liquid, solid, stone, mineral, and so forth. It has been done by several companies for its processing. The purpose of this research is to: 1) know how to do the design on inclined vibrating screen; and 2) know what parameters are needed to design an incined vibrating screen build. Research done by conducting literature study first. Next, determine the model and capacity of vibrating screen to be made. The next stage is data collection and modeling tool design. Next calculate and analyze capacity requirements, structural strength and vibration. The results showed that: 1) designing inclined vibrating screen constructions to be considered several things, namely: media/capacity size and shape, density, moisture, size distribution, and construction; and 2) parameters to note is the probability to filter for 0.999992; filtering performance of 0.01704 m/s²; depth of filtration of 0.5 m; spring stiffness of 2,000 kg/cm; with a spring and wire diameter of 14.5 mm and 2.125 mm.